Strategic foresight in One CGIAR: Gaps and needs in approaches and capacity - Prager, Steven D.; Wiebe, Keith D. (International Food Policy Research Institute, 2022)
This synthesis brief draws on an extensive body of published studies and the latest working papers produced as part of foresight-related research supported by the CGIAR Research Program on Policies, Institutions, and Markets (PIM). It offers a focused, forward-looking perspective on key issues to support discussions on food, land, and water systems transformation and the role of foresight in helping better understand our dynamic future.